PENINGKATAN KUALITAS MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DI PAUD - Putriana Safitri; Sabrina Bella Putri; Destri Sugeh Hartini; Abel Agnesia; Fahmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the improvement of the quality of teacher and education personnel management in Early Childhood Education (ECE) through a Systematic Literature Review (SLR) approach. The method used in this research is SLR, which includes planning, literature selection, data analysis, and synthesis of findings from various scientific articles published within the last five years. The data sources were obtained from relevant national and international journals focusing on ECE teacher management. The results of the study indicate that the quality of teacher and education personnel management in ECE still faces several challenges, particularly in teacher competence, human resource management effectiveness, training equity, and the utilization of learning technology. Insufficient teacher competence negatively affects the quality of learning provided to early childhood learners. In addition, unstructured management systems result in ineffective management of educational personnel. On the other hand, continuous professional development and the use of technology have been proven to improve teacher quality, although their implementation is still not evenly distributed. In conclusion, there is a need to strengthen an integrated management system and policy support to sustainably improve the quality of teachers and education personnel in ECE.